Decrement in resting and insulin‐stimulated soleus muscle mitochondrial respiration is an early event in diet‐induced obesity in mice. Issue 3 (24th January 2019) - Brunetta, Henver Simionato; de Paula, Gabriela Cristina; de Oliveira, Jade; Martins, Eduarda Lopes; dos Santos, Gustavo Jorge; Galina, Antonio; Rafacho, Alex; de Bem, Andreza Fabro; Nunes, Everson Araújo
Abstract : New Findings: What is the central question of this study? What are the temporal responses of mitochondrial respiration and mitochondrial responsivity to insulin in soleus muscle fibres from mice during the development of obesity and insulin resistance? What is the main finding and its importance? Short‐ and long‐term feeding with a high‐fat diet markedly reduced soleus mitochondrial respiration and mitochondrial responsivity to insulin before any change in glycogen synthesis. Muscle glycogen synthesis and whole‐body insulin resistance were present after 14 and 28 days, respectively. Our findings highlight the plasticity of mitochondria during the development of obesity and insulin resistance. Abstract: Recently, significant attention has been given to the role of muscle mitochondrial function in the development of insulin resistance associated with obesity. Our aim was to investigate temporal alterations in mitochondrial respiration, H2 O2 emission and mitochondrial responsivity to insulin in permeabilized skeletal muscle fibres during the development of obesity in mice. Male Swiss mice (5–6 weeks old) were fed with a high‐fat diet (60% calories from fat) or standard diet for 7, 14 or 28 days to induce obesity and insulin resistance. Diet‐induced obese (DIO) mice presented with reduced glucose tolerance and hyperinsulinaemia after 7 days of high‐fat diet. After 14 days, the expected increase in muscle glycogen content after systemic injection of glucose and insulin was not observed in DIO mice. At 28 days, blood glucose decay after insulin injection was significantly impaired. Complex I (pyruvate + malate) and II (succinate)‐linked respiration and oxidative phosphorylation (ADP) were decreased after 7 days of high‐fat diet and remained low in DIO mice after 14 and 28 days of treatment. Moreover, mitochondria from DIO mice were incapable of increasing respiratory coupling and ADP responsivity after insulin stimulation in all observed periods. Markers of mitochondrial content were reduced only after 28 days of treatment. The mitochondrial H2 O2 emission profile varied during the time course of DIO, with a reduction of H2 O2 emission in the early stages of DIO and an increased emission after 28 days of treatment. Our data demonstrate that DIO promotes transitory alterations in mitochondrial physiology during the early and late stages of insulin resistance related to obesity. Abstract :